Outbreak of severe acute respiratory infection in Southern Province, Sri Lanka in 2018: a cross-sectional study - L Gayani Tillekeratne; Ajith Nagahawatte; Ruvini Kurukulasooriya; Christopher W Woods; Sky Vanderburg; Gaya Wijayaratne; Nayomi Danthanarayana; Jude Jayamaha; Bhagya Piyasiri; Chathurangi Halloluwa; Tianchen Sheng; Sujeewa Amarasena; et al. (BMJ Open)
Objectives To determine aetiology of illness among children and adults presenting during outbreak of severe respiratory illness in Southern Province, Sri Lanka, in 2018.Design Prospective, cross-sectional study.Setting 1600-bed, public, tertiary care hospital in Southern Province, Sri Lanka.Participants 410 consecutive patients, including 371 children and 39 adults, who were admitted with suspected viral pneumonia (passive surveillance) or who met case definition for acute respiratory illness (active surveillance) in May to June 2018.Results We found that cocirculation of influenza A (22.6% of cases), respiratory syncytial virus (27.8%) and adenovirus (AdV) (30.7%; type B3) was responsible for the outbreak. Mortality was noted in 4.5% of paediatric cases identified during active surveillance. Virus type and viral coinfection were not significantly associated with mortality.Conclusions This is the first report of intense cocirculation of multiple respiratory viruses as a cause of an outbreak of severe acute respiratory illness in Sri Lanka, and the first time that AdV has been documented as a cause of a respiratory outbreak in the country. Our results emphasise the need for continued vigilance in surveying for known and emerging respiratory viruses in the tropics.